Sustainable finance taxonomies: Enabling the transition towards net zero? Transition score for international frameworks - Catherine Marchewitz; Fernanda Ballesteros; Franziska Schütze; Nesrine Hadj Arab (Deutsches Institut für Wirtschaftsforschung (DIW), 2024)
A plethora of sustainable finance taxonomies are emerging worldwide to support shifting trillions for climate action. Employing a qualitative research approach, we use document analysis to assess 26 sustainable finance taxonomy frameworks worldwide that are in the developing phase or have been published and/or adopted. Based on literature and data we build a transition score (TS) to evaluate the framework's contribution to transition to climate neutrality. We find that only few taxonomies meet most of our criteria for supporting the transition to carbon neutrality, although they are well embedded in environmental policy goals and cover the most important sectors in terms of emissions. The screening approach for economic activities is often not dynamic or aligned with a clear path to climate neutrality and the frameworks target often only specific financial products or a limited group of market participants. Most sustainable finance taxonomies do not carry disclosure and reporting obligations.
Keywords: G18; P00; Q01; Q58; 330; Sustainable Finance Taxonomy; Green Finance; Transition Finance; EU Taxonomy; climate policy; transition plans